2015
DOI: 10.1080/22201181.2015.1075937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine versus midazolam for intranasal premedication in children posted for elective surgery: a double-blind, randomised study

Abstract: Objective: The aim of this study was to compare the effect of dexmedetomidine with midazolam for intranasal premedication in children posted for elective surgery. Trial design: This was a prospective, randomised, double-blinded clinical study. Method: 60 children, 3 to 10 years of age, with American Society of Anaesthesiologists (ASA) physical status I, scheduled for elective surgery, were randomly divided into two groups, group D (dexmedetomidine) and group M (midazolam). Group D patients received intranasal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…The included articles were undertaken from 2008-2016 in eight different countries: USA (one), Turkey (one), Saudi Arabia (one), India (three), China (three), Egypt (two), Mexico (one), and Oman (one). Four studies 13,18,19,22 compared the effects of intranasal dexmedetomidine with those of oral midazolam, and six studies 10,11,14,16,17,21 compared the effects of intranasal dexmedetomidine with those of intranasal midazolam. One study compared intranasal dexmedetomidine with intranasal clonidine, 15 and two studies compared intranasal dexmedetomidine with intranasal normal saline.…”
Section: Study Characteristics and Patient Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included articles were undertaken from 2008-2016 in eight different countries: USA (one), Turkey (one), Saudi Arabia (one), India (three), China (three), Egypt (two), Mexico (one), and Oman (one). Four studies 13,18,19,22 compared the effects of intranasal dexmedetomidine with those of oral midazolam, and six studies 10,11,14,16,17,21 compared the effects of intranasal dexmedetomidine with those of intranasal midazolam. One study compared intranasal dexmedetomidine with intranasal clonidine, 15 and two studies compared intranasal dexmedetomidine with intranasal normal saline.…”
Section: Study Characteristics and Patient Populationsmentioning
confidence: 99%
“…All of the included studies used a random allocation method. Ten studies [10][11][12][13][14][15][16][17][18]22 described the allocation concealment in detail, and six studies 10,11,13,15,16,22 concretely explained their blinding methods. The risk of allocation concealment and blinding was unclear in the other studies.…”
Section: Quality Of the Included Studiesmentioning
confidence: 99%
“…21 and Pasin L. compared dexmedetomidine with midazolam as a premedication in their meta-analysis; their results concluded that dexmedetomidine premedication resulted in a better sedative and anxiolytic effect during parent separation. In a study by Singlaa D. 15 , a double-blind, randomised study to compare dexmedetomidine versus midazolam for intranasal premedication in children posted for elective surgery. Dexmedetomidine resulted in better mask acceptance score than intranasal midazolam; similar results were seen in a study conducted by Seyedeh Z to compare oral Dexmedetomidine versus Midazolam as Anaesthetic Premedication in Children.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Anxiety during separation was evaluated by parent separation anxiety score. 14,15 Mask acceptance was evaluated by mask acceptance score. 14,15,16 While wake up behaviour was evaluated by wake up score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation